THE GEOPOLITICAL IMPLICATION OF THE ZANGAZUR CORRIDOR: A DRIVER FOR REGIONAL ADVANCEMENT AND LINKAGE - Muhammad Gulahmadov; Nargiz Hajiyeva (Agora International Journal of Economical Sciences, 2023)
This research delves into the geopolitical role of the Zangazur Corridor in the recently liberated territories of Azerbaijan, examining its potential as a catalyst for regional development and enhanced connectivity. Employing the gravity model, the study investigates the corridor's influence on economic growth, trade facilitation, and geopolitical dynamics among Azerbaijan, Armenia, Georgia, Iran, and Türkiye. The comprehensive methodology incorporates a detailed literature review, geopolitical analyses, and economic assessments. Through this approach, the study amalgamates historical, economic, and geopolitical insights, comprehensively understanding the corridor's implications on regional integration. The main results underscore the Zangazur Corridor as a transformative conduit, pivotal in fostering economic opportunities and enhancing regional connections. It depicts the corridor's capacity to fortify trade routes, reshape infrastructure, and bolster regional cooperation. The study also explores the geopolitical implications, presenting the challenges and opportunities arising from this infrastructure project. This article offers a nuanced understanding of the corridor's potential transformative impact on economic synergies within the South Caucasus nations. It culminates in a comprehensive evaluation of the Zangazur Corridor's role in the region's economic and geopolitical landscape.